Exacerbação da doença pulmonar obstrutiva crônica : investigação do efeito sobre a modulação autonômica cardíaca e capacidade funcional - Kabbach, Erika Zavaglia (2017)
Chronic obstructive pulmonary disease (COPD) is a major cause of disability, hospital admissions, and the demand for care in health systems. Periods of exacerbations are frequent and are associated with increased risk for cardiovascular disease and reduced overall health status. The involvement of cardiac autonomic modulation (CAM) has been evidenced in this population in stable periods; however, knowledge about CAM in exacerbated hospitalized COPD, as well as on the influence of functional aspects in this function is still scarce. In this context, of exacerbation of COPD and the possibility of advancing the knowledge about the cardiac autonomic nervous system and the functional capacity in this clinical condition motivated the development of this dissertation, which will consist of the presentation of a study titled " Increased parasympathetic cardiac modulation in patients with acute exacerbation of chronic obstructive pulmonary disease: how should we interpret it?". The aim of this study was to evaluate MAC responses in patients with COPD during exacerbation of the disease compared to patients in stable condition and to verify the possible association of these responses with functional capacity. Patients with COPD were included in the study and divided into two groups according to the clinical condition: stable and exacerbated. The exacerbated patients were evaluated in the first 24-48 hours after initiation of pharmacological therapy for exacerbation. The HR signal and the RR intervals were recorded for 10 minutes in seated position for later analysis of MAC using heart rate variability (HRV) indices. Clinical and functional data were obtained by evaluating handgrip strength, dyspnea and general health status. Our results showed higher values of the representative indices of the parasympathetic modulation for the exacerbated patients compared to the stable patients: RMSSD (17.8 ± 5.6 vs 11.7 ± 9.5 ms); HF (111.3 ± 74.9 vs. 45.6 ± 80.7 ms2); SD1 (12.7 ± 3.9 vs. 8.3 ± 6.7 ms). Significant and negative associations between HF and handgrip strength (r = -0.58) and LF with dyspnea were found (r = -0.53) (P <0.05). These findings can be attributed, among other factors, to the influence of vagal activity on the respiratory system, which results in narrowing of the airways and consequent worse clinical status. Reinforcing these findings it was possible to verify that the parasympathetic modulation is inversely associated to the functional capacity in the exacerbation of the disease. These results add knowledge that may be useful to the clinical practice of the professional involved in the care of this patient.